Changes in Home Parenteral Nutrition Practice Based on the Canadian Home Parenteral Nutrition Patient Registry. (25th September 2015) - Hortencio, Taís Daiene Russo; Arendt, Bianca Maria; Teterina, Anastasia; Jeejeebhoy, Khursheed N.; Gramlich, Leah M.; Whittaker, J. Scott; Armstrong, David; Raman, Maitreyi; Nogueira, Roberto José Negrão; Allard, Johane P.
Abstract : Background: Since 2005, the Canadian home parenteral nutrition (HPN) registry has collected data on patients' demography, outcomes, and HPN clinical practice. At annual meetings, Canadian HPN programs review and discuss results. Aim: To evaluate changes over time in patient demography, outcomes, and HPN clinical practice using the registry data. Methods: This retrospective study evaluated 369 patients who were prospectively entered in the registry. Two periods were compared for the first data entry: 2005–2008 (n = 182) and 2011–2014 (n = 187). Patient demography, indications for HPN, HPN regimen, nutrition assessment, vascular access, and number of line sepsis per 1000 catheter days were evaluated. Results: For 2011–2014 compared with 2005–2008, indications for HPN changed significantly, with an increased proportion of patients with cancer (37.9% vs 16.7%) and with fewer cases of short bowel syndrome (32% vs 65.5%); line sepsis rate decreased from 1.58 to 0.97 per 1000 catheter days; and the use of tunneled catheters decreased from 64.3% to 38.0% and was no longer the most frequently chosen vascular access method. In contrast, the proportion of peripherally inserted central catheters increased from 21.6% to 52.9%. In addition, there was a reduction in number and days of hospitalizations related to HPN, and favorable changes were noted in the prescription of energy, proteins, and trace elements. Conclusion: The Canadian HPN registry is useful in tracking trends in demography, outcomes, and clinical practice. Results suggest a shift in patient demography and line access with improvement in line sepsis, hospitalizations, and HPN prescriptions.